1986
DOI: 10.1007/bf01880760
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of gas exchange by automated analysis of O2 and CO2 alveolar to arterial differences

Abstract: A computer program to measure breath by breath alveolar pressure (PA) and alveolar to arterial difference (AaD) for O2 and CO2, by a mass-spectrometer has been implemented. The program allows the determination of alveolar gas by different methods: 1. Bohr's equation (BE); 2. ideal alveolar air equation for O2 (IDO2); 3. end-tidal (ET); 4. by the Rahn's definition of 'mean alveolar gas', i.e., alveolar pressures are defined when instantaneous respiratory exchange ratio (IRQ) equals mean respiratory exchange rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Pulmonary gas exchange was estimated primarily by the V D/VTalv, calculated using etCO2 in the Severinghaus equation (1,14,25). Use of the etCO2 to estimate the alveolar dead space fraction as opposed to the mixed-expired CO2 was chosen because the end-tidal equation provides a more specific estimate of the alveolar dead space fraction compared with the physiological dead space fraction, which measures both airway and alveolar dead space (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary gas exchange was estimated primarily by the V D/VTalv, calculated using etCO2 in the Severinghaus equation (1,14,25). Use of the etCO2 to estimate the alveolar dead space fraction as opposed to the mixed-expired CO2 was chosen because the end-tidal equation provides a more specific estimate of the alveolar dead space fraction compared with the physiological dead space fraction, which measures both airway and alveolar dead space (25).…”
Section: Methodsmentioning
confidence: 99%
“…Use of the etCO2 to estimate the alveolar dead space fraction as opposed to the mixed-expired CO2 was chosen because the end-tidal equation provides a more specific estimate of the alveolar dead space fraction compared with the physiological dead space fraction, which measures both airway and alveolar dead space (25). VD/VTalv correlates with pulmonary vascular resistance (22), and perfusion defects in humans with PE (17) decreases in parallel with reduction in perfusion defects during treatment (25) and correlates with the plasma concentration of TxB2 in dogs with PE (39).…”
Section: Methodsmentioning
confidence: 99%
“…From 13 unique candidate variables, our selection process found that end-tidal CO 2 , end-tidal O 2 , and flow yielded the genome with highest overall diagnostic accuracy. End-tidal CO 2 concentrations have previously been used to diagnose pulmonary embolism [11,20]. Similarly, higher end-tidal O 2 concentrations are associated with pulmonary embolism [11].…”
Section: Discussionmentioning
confidence: 99%
“…The D-dimer test has excellent diagnostic sensitivity but has poor specificity in most patients with risk factors for pulmonary embolism [5]. Several studies have been conducted utilizing the knowledge that pulmonary embolism increases pulmonary deadspace and affects partial pressures of exhaled CO 2 or O 2 [11,20]. Recently, development of a portable device that measures exhaled CO 2 and O 2 concentrations along with flows and volumes has shown promise in predicting thromboembolism [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other drawbacks to the use of the Enghoff equation include the requirement for a painful arterial blood gas stick, and the occurrence of negative values suggesting non-steady-state collection of end-tidal CO 2 and arterial blood pCO 2 (Kline et al, 2004). Prior work has provided concept framework suggesting that end-tidal CO 2 decreases and end-tidal O 2 increases in rats subjected to experimental PE, and in humans diagnosed with pulmonary thromboembolism (Paoletti et al, 1986;Jones et al, 2003). This project was designed to non-invasively measure the effect of high ventilation-perfusion relationships imparted by pulmonary thromboembolism by measuring the decrease without the need for arterial blood gas sampling.…”
Section: Discussionmentioning
confidence: 99%